Implementation Of The Pancasila Student Profile Strenghening Project (P5) In The Independent Curriculum In High Schools - Ritagustiani Ritagustiani; Erianjoni Erianjoni; Junaidi Indrawadi; Eka Asih Febriani (Dinasti International Journal of Education Management And Social Science, 2025)
The purpose of this study is to provide an overview of the successful implementation of the Pancasila Student Profile Strengthening Project (P5) in Senior High Schools through a literature review of several related articles. The research method used is library research by accessing the Google Scholar database using the keywords "Implementation" and "Pancasila Student Profile Strengthening Project". The results of the study show that the readiness of schools, teachers, supervision, and students greatly affects the success of the implementation of P5. Schools need to provide adequate facilities, involve school committees and communities in planning, and periodically evaluate programs. Teachers play an important role in the implementation of P5, so it is necessary to receive training to understand the preparation of modules, develop learning methods, and master contextual principles, holistic, exploratory, and student-centered. These principles encourage students to be more active, creative, and independent in the learning process. In addition, internal and external supervision is also an important supporting factor. School supervisors provide direction and motivation, while principals and teachers guide and monitor the course of student activities. Structured oversight helps identify constraints and provide timely solutions. With good support from all elements of the school, the implementation of P5 can run more optimally, allowing students to develop academic competence, social skills, and character in accordance with the values of Pancasila, which is the main foundation of education in Indonesia.